A comprehensive review on Gossypium hirsutum resistance against cotton leaf curl virus - Nadeem, Sahar; Riaz Ahmed, Syed; Luqman, Tahira; Tan, Daniel K. Y.; Maryum, Zahra; Akhtar, Khalid Pervaiz; Muhy Ud Din Khan, Sana; Tariq, Muhammad Sayyam; Muhammad, Nazar; Khan, Muhammad Kashif Riaz; Liu, Yongming (Frontiers in Genetics, 2024)
CLCuV is a well-known drastic plant viral disease, destroying cotton production worldwide. Recently, this disease has again become an emerging threat to cotton production in Asia and other cotton-growing regions. The last few decades have witnessed the destruction of cotton production in Asia, Africa, and the USA due to CLCuV. Scientists have invented and applied different tools to combat CLCuV, but these techniques were time-consuming, laborious, and less effective. Our article deals with deep information on cotton evaluation, CLCuV emergence, and current status, and deep insight into molecular solutions to deal with CLCuV in more effective ways within a very short period. As of our knowledge, this is the review article that provides genomic solutions in cotton to deal with CLCuV. Keeping in view the genetic background of our article we are confident that this journal is a perfect fit for our article and will not only increase the journal citations but also help the molecular breeders to find solutions to combat CLCuV.